Reflections on Individual Personal Values in the Budgetary Slack Phenomenon - Putu Yunartha Pradnyana Putra; Farah Nisa Ul Albab; Christopher Clark Aditya Swara (The Indonesian Journal of Accounting Research, 2019)
Abstract: Research and theory on the role of personal values in morality have received significant attention in the last years. In this study, we observe the tendency of individuals acting within organizations to create budgetary slack given their personal values and social reality. Specifically, we interview with the four undergraduate students in Accounting. We observe the ethical dilemma of the students as a representative of youth who ever involved in the budget-setting process. Recent studies in empathy-related responses to the individual ethical dilemma are also discussed. We find that all the participants have different responses to slack the budget after being pressured by their social environment. All the participants tend to create a budget slack by adding unexpected costs in their budgets. They use the